Spectrum of lung, liver and kidney pathology in autopsy cases: a study at a tertiary center - Borah, Karan K.; Thakuria, Dipankar; Saikia, Projnan; Borsaikia, Kusum (International Journal of Research in Medical Sciences, 2024)
Background: Autopsy, particularly pathological autopsy, plays a crucial role in understanding the causes of death and disease processes that lead to mortality. This retrospective study aimed to analyze the prevalence, patterns, and etiological factors of lung, liver, and kidney injuries in autopsy cases conducted at Jorhat Medical College and Hospital, Assam, from January 2019 to October 2023. Methods: A total of 90 cases were included, comprising various causes of death, excluding decomposed bodies and cases primarily due to extensive trauma. Histopathological analysis was conducted on tissue samples collected by forensic experts. Results: Lung pathology was more common in males, with congestion and inflammation being predominant, possibly attributed to pneumonia and tuberculosis. Liver diseases, predominantly affecting males, showed frequent steatosis and cirrhosis. Notably, Langhans giant cells with necrosis were observed in 4.65% of cases. Renal pathology revealed predominant changes in tubular and interstitial tissue, including hydropic changes, intertubular hemorrhage, congestion, glomerulosclerosis, acute tubular necrosis, pyelonephritis, and malignancy. Conclusions: The study findings emphasizes the importance of autopsy in elucidating the spectrum of lung, liver, and kidney injuries, providing insights into the demographic associations and underlying etiological factors. These findings have significant implications for understanding disease prevalence, guiding clinical management, and informing public health strategies. Further research focusing on preventive measures and early detection of these pathologies is warranted to mitigate their impact on mortality and morbidity.